THE LOCAL CONTENTS OF INDONESIA’S NICKEL MINING COMPANIES - Ijang Suherman; Ridwan Saleh (Indonesian Mining Journal, 2015)
Analysis on the local content of Indonesia mineral mining company is intended to provide input in compiling draft regulation of the Minister of Energy and Mineral Resources regarding the use of domestic goods and services in mineral and coal mining activities, as a follow up the implementation of Government Regulation Number 23/2010 Article 88. A direct sampling survey was conducted to several nickel mining companies. The results showed that the local content for groups of goods and services at PT Vale Indonesia were 51.04% and 46.06% respectively, while at PT Antam Tbk. was 100% (groups of goods) and 99.6% (services). Based on national labour aspect, the local contents of five companies were relatively high, namely 98.63%, however, those came from province and regency areas were only 67,97% and 39.20% respectively. PT Vale Indonesia empowered 84.41% local manpowers from Sorowako area with the measured local content of nickel matte around 43.59%. The measure local content indicated that there was a big opportunity to increase the local content. Some factors that inhibited the effort to increase the use of domestic products included not smoothly the information flow, opportunities and transparency of product testing, the requirements of the Indonesia National Standard, the price preference in the tender process, tax issues, permit dangerous products as well as human resources issues.